2000
DOI: 10.1111/j.1740-8261.2000.tb02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Features of Brain Stem Abscessation in Two Cats

Abstract: Premortem magnetic resonance imaging (MRI) was performed in two cats with brain stem abscessation confirmed post mortem by histology and recovery of multiple bacterial species. The MRI features of the abscesses were distinctive and included a thick and marked enhancement of the abscess capsule and extension of the lesion from a tympanic bulla in one cat. A focal area of increased signal intensity was present on T2-weighted images. A circumscribed area of decreased signal intensity was surrounded by a ring of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 41 publications
(19 reference statements)
4
52
0
Order By: Relevance
“…The MR appearance of the abscess in this case is typical of a mature brain abscess, including pockets of T2-hyperintense material surrounded by a T2-hypointense rim, large amounts of vasogenic edema, and strong peripheral contrast enhancement [7][8][9]. One apparently distinct and as yet unexplained MRI feature of brain abscesses that was present in this case is the appearance of multiple rims on T2-weighted sequences (Figure 1(a) and inset).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MR appearance of the abscess in this case is typical of a mature brain abscess, including pockets of T2-hyperintense material surrounded by a T2-hypointense rim, large amounts of vasogenic edema, and strong peripheral contrast enhancement [7][8][9]. One apparently distinct and as yet unexplained MRI feature of brain abscesses that was present in this case is the appearance of multiple rims on T2-weighted sequences (Figure 1(a) and inset).…”
Section: Discussionmentioning
confidence: 99%
“…CT and MRI characteristics of brain abscesses have been described in humans and domestic animals [1][2][3][4][5][6][7][8]. The MR appearance of the abscess in this case is typical of a mature brain abscess, including pockets of T2-hyperintense material surrounded by a T2-hypointense rim, large amounts of vasogenic edema, and strong peripheral contrast enhancement [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…In 10 cats for which the outcome was reported, 2/10 (20%) recovered with no residual neurologic deficits, 2/ 10 (20%) recovered with persistent neurologic deficits, 4/ 10 (40%) were euthanized because of clinical deterioration, and 2/10 (20%) died. 6,[11][12][13][14][15][16][17] The high mortality associated with bacterial CNS infections is because of the difficulty of diagnosing the disease, which results in delayed or inappropriate therapy. One recent study of cats with inflammatory CNS disease found that an antemortem diagnosis could not be made in 18/62 (29%) cases.…”
mentioning
confidence: 99%
“…CSF results are available for 5 cats with bacterial CNS infection, and all of these cases had increased numbers of WBC (75-42,750/mL) and neutrophilic pleocytosis (55-100%), with increased protein concentrations (94-620 mg/dL) in their CSF. 10,12,14,15,17 The association between suppurative inflammation and bacterial CNS infection leads many clinicians to treat patients empirically with antibiotics, even when CSF cultures are negative. The choice of antibiotic is complicated by the fact that many species of bacteria can cause CNS infections in cats.…”
mentioning
confidence: 99%
See 1 more Smart Citation